2021
DOI: 10.3389/froh.2021.735634
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maternal Infections and Inflammatory Responses on Craniofacial Development

Abstract: Pregnancy is a tightly regulated immunological state. Mild environmental perturbations can affect the developing fetus significantly. Infections can elicit severe immunological cascades in the mother's body as well as the developing fetus. Maternal infections and resulting inflammatory responses can mediate epigenetic changes in the fetal genome, depending on the developmental stage. The craniofacial development begins at the early stages of embryogenesis. In this review, we will discuss the immunology of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 318 publications
(328 reference statements)
0
3
0
Order By: Relevance
“…An association between the development of OFC and maternal illness and infections has previously been described. Studies in Latin America showed that maternal acute and chronic viral infections were significantly associated with the incidence of cleft lip cases, which is hypothesized to be secondary to vascular disruption during the embryonic period associated either with hyperthermia and/or the use of salicylates 16 . Half of our cohort experienced upper urinary tract infections; however, pathogen identification was not recorded.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…An association between the development of OFC and maternal illness and infections has previously been described. Studies in Latin America showed that maternal acute and chronic viral infections were significantly associated with the incidence of cleft lip cases, which is hypothesized to be secondary to vascular disruption during the embryonic period associated either with hyperthermia and/or the use of salicylates 16 . Half of our cohort experienced upper urinary tract infections; however, pathogen identification was not recorded.…”
Section: Discussionmentioning
confidence: 81%
“…Studies in Latin America showed that maternal acute and chronic viral infections were significantly associated with the incidence of cleft lip cases, which is hypothesized to be secondary to vascular disruption during the embryonic period associated either with hyperthermia and/or the use of salicylates. 16 Half of our cohort experienced upper urinary tract infections; however, pathogen identification was not recorded. Other studies have reported a larger association with Chlamydia exposure, apparently secondary to the 60 kD heat shock protein (hsp60), considered a potent inflammation inducer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, epidemiological studies have associated pro-inflammatory conditions as diabetes, maternal infections, and obesity to CLP 29 37 , however, with no experimental demonstration of how those risk factor could affect craniofacial development. Concurrently, there is evidence that pro-inflammatory activation modulates CDH1 /E-cadherin levels in multiple cell models 38 45 .…”
Section: Introductionmentioning
confidence: 99%